Downstream processing in developing countries: Opportunity or mirage? - James Bond (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2013)
Downstream processing of oil, gas and minerals does not contribute nearly as much to the local economy as many leaders of resource-rich countries believe. A better strategy than promoting foreign investment in downstream processing is to nurture clusters of resource-related firms by creating a business-friendly investment environment and investing in targeted infrastructure.
Keywords: 330